CLASSIFICATION OF QUANTITATIVE MODEL SCENARIOS IN A CLOSED-LOOP SUPPLY CHAIN USING UNDERLYING FACTORS AND VARIABLES: A RESEARCH REVIEW - Yuliawati, Evi; Pratikto, Pratikto; Sugiono, Sugiono; Novareza, Oyong (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2022)
In a closed-loop supply chain area, the concept of sustainability is one of the primary factors that motivates companies to survive in a dynamic market. The purpose of this paper is to present a literature review of quantitative models in the remanufacturing process, especially mathematical models such as pricing decisions and cost models, reviewed from various scientific journals. Challenges to meet market demands, to boost efficient operational costs, and to increase profits have made researchers interested in deeply exploring this issue. Studies in the reverse supply chain area ensure that the supply process runs effectively and efficiently, meeting a level that is as good as when implementing the forward supply chain. Coordination and collaboration among companies, core acquisition strategy, model character behavior, and reverse channel structure are some characteristics of the quantitative models within the area of a closed-loop supply chain. Mapping was arranged to identify the involvement of research variables (core acquisition cost and remanufactured product price) and factors that were considered in the mathematical model of core acquisition (quantity and quality). Furthermore, the related literature on the issue was analyzed based on the involvement of the considered variables and factors. Finally, future research opportunities are presented as the result of the conducted literature review in this study.